[Bus at Landmannalaugar Area] - Streng, Evelyn Fiedler (1975)
Photograph of a bus parked along a lake at Landmannalaugar. The blue lake sits in a valley of round, brown and green mountains. The light blue and white bus sits to the right beside a patch of red stone along the mountain on the right edge of the photograph. Groups of people stand along hills in the foreground while an individual in orange stands beside the bus.